Formulating Positive Public Administration in Indonesia: An Actor, Structure, Discourse Analysis - Amalia Putri, Rizky; Petrus Likuwatan Werang, Nicolaus; Lusiana Florentin Werang, Maria (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
The changing paradigm of global public administration, from classical and managerial approaches to collaborative governance, indicates that the development of this discipline does not occur linearly, but is shaped by the relationships between actors, structures, and discourses. In the Indonesian context, the adoption of global paradigms is often carried out normatively, without adequate contextualization, leading to a lack of alignment with local socio-political characteristics and values. This study employed an interpretive, conceptual literature review of journal articles, academic books, and policy documents. These sources were examined through thematic categorization and conceptual synthesis to navigate how the interaction of actors, structures, and discourses shapes bureaucratic modernization, strengthening planning institutions and development administration in Indonesia. The essay reveals three primary findings. First, bureaucratic modernization is dominated by discourses of efficiency and performance that strengthen formal structures but limit innovation by local actors. Second, planning institutions develop within a technocratic regulatory scheme, thus limiting substantive participation. Third, development administration adopts global governance discourses without systematically integrating collective values such as cooperation and deliberation. Based on these findings, this essay proposes a “positive public administration” scheme that emphasizes contextuality, inclusiveness, and cultural sensitivity as the direction for developing public administration in Indonesia.